The Effect of TBL (task based learning) on improving students’ oral communication skills - Mostafa ali kulaib (Journal of Libyan Academy Bani Walid, 2025)
The effectiveness of Task-Based Learning (TBL) in enhancing the oral communication skills of Libyan English as a Foreign Language (EFL) learners is investigated in this study. Many Libyan students still struggle with speaking English, particularly with fluency and confidence, despite having taken numerous English language courses. Using a non-equivalent group strategy and a mixed-methods quasi-experimental design, this study assessed communicative ability using pre- and post-tests. Fifty El-Mergib University first-year students" According to the results of the post-test, the experimental group outperformed the control group in every category that was measured, including vocabulary, grammar, fluency, and comprehension. This noteworthy improvement, as shown by the experimental group’s computed t-value of 70.253 (p < 0.01), highlights TBL’s ability to tackle particular issues like hesitancy and insecurity that are common among Libyan EFL learners. TBL is a very successful pedagogical strategy for developing authentic communicative competence in the Libyan EFL context, according to the study’s findings, and its wider implementation could greatly improve students’ practical English speaking skills.